Problematizing the authentic self in conceptualizations of emotional dissonance. (September 2019) - O'Brien, Elaine; Linehan, Carol
With exhortations to be 'your authentic self' proliferating in workplaces what does this mean for emotion and identity management at work? This article explores the relationship between emotional labour and identity. It focuses on the tension or 'emotional dissonance' that can be experienced when a job role requires the display of organizationally appropriate emotions. Experiences of emotional dissonance are examined through in-depth interviews and diary study with human resource professionals. We tease out the contradictions participants are immersed in, the affective sensemaking they engage in about such contradictions and demonstrate the individual's capacity for multiple selves to address contextual demands. From this, a new conceptual lens on emotional dissonance is proposed. Conventional conceptualizations view dissonance as a clash between 'real' and 'false' emotion predicated on an authentic self that is transmuted in organizational settings. Our theoretical contribution is to argue that emotional dissonance arises from the struggle to construct a situationally salient self in the face of conflicting emotions and loyalties to competing selves and values. The struggle in emotional labour is not with 'the truth of oneself' but rather with identifying which self to foreground in a given situation.